2011
DOI: 10.1074/jbc.m110.182014
|View full text |Cite
|
Sign up to set email alerts
|

Converting the Highly Amyloidogenic Human Calcitonin into a Powerful Fibril Inhibitor by Three-dimensional Structure Homology with a Non-amyloidogenic Analogue

Abstract: Irreversible aggregation limits bioavailability and therapeutic activity of protein-based drugs. Here we show that an aggregation-resistant mutant can be engineered by structural homology with a non-amyloidogenic analogue and that the aggregation-resistant variant may act as an inhibitor. This strategy has successfully been applied to the amyloidogenic human calcitonin (hCT). Including only five residues from the non-amyloidogenic salmon calcitonin (sCT), we obtained a variant, polar human calcitonin (phCT), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
93
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(102 citation statements)
references
References 73 publications
8
93
1
Order By: Relevance
“…At low pH, hCT fibrillation is slowed by Asp 15 protonation (32). The decreased fibrillation propensity of sCT is attributed to the increased number of polar amino acids compared with hCT (33). Our results show that this barrier to fibrillation can be overcome by introducing GAG as an electrostatic binding partner for excess positive charges.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…At low pH, hCT fibrillation is slowed by Asp 15 protonation (32). The decreased fibrillation propensity of sCT is attributed to the increased number of polar amino acids compared with hCT (33). Our results show that this barrier to fibrillation can be overcome by introducing GAG as an electrostatic binding partner for excess positive charges.…”
mentioning
confidence: 63%
“…We suggest sCT-NH 2 to have Lys 11 placed in the fibril interior in a face-to-face arrangement (pairing ␤-stands are found in the same conformation and arranged with the same residues in the interior of the structure) stabilized by a salt bridge to Glu 15 . Biological Implications-sCT is known to be less fibrillationprone than hCT because of the increased polarity of sCT (33). Lowering the pH increases the polarity of the peptide due to His protonation, and hence both hCT and sCT are expected to be less fibrillation-prone at low pH.…”
Section: Combining CD and Saxs Data Provides Structural Information Amentioning
confidence: 99%
“…Based on the number, location, and relative abundance of Lys residues in each protein (Table 3 and Supplementary Figure S3), we expected that CLR01 would inhibit the aggregation of α-synuclein, insulin, β 2 m, TTR, and lysozyme, but not of IAPP, which contains a single Lys residue at position 1. CT also has only one Lys residue, but this residue, Lys18, is within a sequence previously reported to be important for amyloid formation 3133 and therefore, we predicted that CLR01 might be able to inhibit CT aggregation. It was difficult to predict the impact of CLR01 on PrP(106–126), which has two Lys residues corresponding to 9.5% of its sequence, but are located in positions 1 and 5, away from the hydrophobic, amyloidogenic region at the C-terminus.…”
Section: Resultsmentioning
confidence: 92%
“…The unstructured nature of the CT C‐terminus, along with the lack of sequence conservation between species, suggests a minimal role in receptor activation ,,. C‐terminally mutated hCT peptides have shown no decrease in receptor binding or hypocalcemic effect, calling into question whether or not the binding exhibited by Johansson and Lee was sufficient for receptor activation ,. The use of truncated versions of sCT and CTR by Johansson and Lee, along with the lack of a membrane environment and nonevaluation of activation also presents questions as to the biological relevance of the interactions observed ,.…”
Section: Role Of Calcitonin Structure and Aggregation In Biological Fmentioning
confidence: 99%
“…Additionally, more of this α‐helix promoting hCT mutant remained soluble once aggregation was completed, compared with wild‐type, and the peptide modifications did not adversely affect receptor binding or the hypocalcemic effect. Another study by Andreotti and colleagues found that the mutation of five central and C‐terminally located residues in hCT to their sCT equivalents (Y12L, N17H, A26N, I27T, A31T) both decreased the rate of aggregation and maintained structure and biological function . This modified hCT also had the ability to inhibit the aggregation of wild‐type hCT when the two were coincubated .…”
Section: Role Of Calcitonin Structure and Aggregation In Biological Fmentioning
confidence: 99%